Structure-Function insights of Jaburetox and Soyuretox: Novel intrinsically disordered polypeptides derived from plant ureases - Grahl, Matheus V. Coste (2020)
Intrinsically disordered proteins (IDPs) and intrinsically disordered regions (IDRs) do not have a stable 3D structure but still have important biological activities. Jaburetox is a recombinant peptide derived from the jack bean (Canavalia ensiformis) urease and presents entomotoxic and antimicrobial actions. The structure of Jaburetox was elucidated using nuclear magnetic resonance which reveals it is an IDP with small amounts of secondary structure. Different approaches have demonstrated that Jaburetox acquires certain folding upon interaction with lipid membranes, a characteristic commonly found in other IDPs and usually important for their biological functions. Soyuretox, a recombinant peptide derived from the soybean (Glycine max) ubiquitous urease and homologous to Jaburetox, was also characterized for its biological activities and structural properties. Soyuretox is also an IDP, presenting more secondary structure in comparison with Jaburetox and similar entomotoxic and fungitoxic effects. Moreover, Soyuretox was found to be nontoxic to zebra fish, while Jaburetox was innocuous to mice and rats. This profile of toxicity affecting detrimental species without damaging mammals or the environment qualified them to be used in biotechnological applications. Both peptides were employed to develop transgenic crops and these plants were active against insects and nematodes, unveiling their immense potentiality for field applications.